Analysis of the perceptions of flood and effect of adoption of adaptation strategies on income of informal settlements of Mamelodi in South Africa - Nyam, Y.S.; Modiba, N.T.S.; Ojo, T.O.; Ogundeji, A.A.; Okolie, C.C.; Selelo, O.T. (Elsevier, 2024)
Extreme weather events are being experienced all over the world because of climate change, posing challenges for individuals and households who rely on agricultural operations as their major source of livelihood. Household-level adaptation is an efficient way of dealing with global climate change. As such, this study aims to examine the perception of informal settlers to flood risk and their adoption of adaptation strategies to flood. This study applied the seemingly unrelated regression (SUR) to identify factors influencing the perception of flooding on community members and probit regression to identify the factors influencing the adoption of adaptation strategies to floods and examined the impact of the adoption of adaptation strategies on income in Eerste Fabriek informal settlement in Mamelodi using two-step quasi-maximum likelihood estimates of fractional response model. Our results show that community members are perceptive of floods and their impact on the environment and their livelihoods, and on average, they believe flood impact is significant. Age, marital status, education, employment status, income, and household size are demographic factors that tend to influence their perception of the impact of flood events. Access to institutional facilities such as health and recreational facilities was also a significant factor in how community members adapt to the impact of floods. Timely healthcare access services are a significant precursor for people to form their perception, which is intended to help them adapt appropriately to situations as health is wealth. Community members' perceptions and adaptive capacity can be improved through policies that foster the adoption of effective adaptation strategies. Community-based adaptation strategies are necessary for involving all stakeholders and necessary for mitigating the effects of flooding.
Keywords: Adaptation strategies; SUR; Eerste Fabriek; fractional response model; informal settlement